2016
DOI: 10.1515/aep-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Content of phenolic compounds in soils originating from two long-term fertilization experiments

Abstract: Abstract:The objective of the study was to compare the impact of three systems of multiannual fertilization applied in two long-term fi eld experiments on the content of phenolic compounds in the soil. In the study, both natural (manure, slurry) and mineral (NPK) fertilizers were used, along with combined, organic-and-mineral fertilization. Experiment I was established in 1972 on grey brown podzolic soil; experiment II, in 1973 on brown soil. In both experiments crops were cultivated in a 7-year rotation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…However, in the LAU soils, the content of TPCs, besides being strongly regulated by TOC, was also significantly (P < 0.01) correlated with the total nitrogen content. Our results agree with those found by Sądej et al (2016). Furthermore, in the LAU soils, there was a slight (P < 0.05) correlation between the WPCs and the clay content (r = 0.38).…”
Section: Quantitative Characterisation Of Soil Phenolic Compounds In Core Drill Samplessupporting
confidence: 92%
“…However, in the LAU soils, the content of TPCs, besides being strongly regulated by TOC, was also significantly (P < 0.01) correlated with the total nitrogen content. Our results agree with those found by Sądej et al (2016). Furthermore, in the LAU soils, there was a slight (P < 0.05) correlation between the WPCs and the clay content (r = 0.38).…”
Section: Quantitative Characterisation Of Soil Phenolic Compounds In Core Drill Samplessupporting
confidence: 92%
“…For the functioning of the ecosystem in Phaeozems, the synthesis/dynamics of microbial biomass and its role in plant nutrition are of particular importance for interpreting the role in determining soil type, in particular, under different conditions of its exploitation, as carbon (C) and nitrogen (N) are the elements mainly involved when discussing microbial biomass. Similar research on other types of soil (grey brown podzolic soil and brown podzolic soil) confirmed connection between the organic carbon and nitrogen content and total phenolic compounds accumulation, differences between the soil types investigated and the source of organic matter or fertilizers input accessible to microbial transformation (15). Authors reported higher total phenolics level and percentage of water -soluble phenols (29.1%) in brown podzolic soil than in grey brown podzolic soil (18.44%).…”
Section: Discussionsupporting
confidence: 63%
“…The phenol content in soil was determined by the oxidation of phenols with the Folin-Ciocalteu reagent and the formation of a colored product whose absorbance was measured spectrophotometrically at 750nm. Organic extracts were obtained from the combination of soil with solvents, acetonemethanol-water in equivalent ratio, centrifuged and analyzed according to the methodology for the content in phenolic compounds (15). Its concentration was calculated according to the calibrated curve for the standard phenolic compound (gallic acid) and the phenolic content of the soil extracts was expressed in mg GAE/g, equivalent gallic acid.…”
Section: Soils Characterizationmentioning
confidence: 99%
“…In addition, those compounds can be produced by the degradation of chlorinated pesticides into the environment and in the presence of chlorine, which is produced during the burning of organic material (Navarro et al 2008, Sądej et al 2016). The phenol features, such as solubility in water and their stability in the environment, could result in the compounds lasting for a long time in the environment and water sources are able to transfer them to long distances (Rappoport 2004).…”
Section: Introductionmentioning
confidence: 99%